Transesophageal Echocardiography for Congenital Heart Disease - Wong, Pierre C.; Miller-Hance, Wanda C.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Transesophageal echocardiography (TEE) has played an instrumental role among the many advances in the field of congenital heart disease (CHD) that have resulted in successful and continually improving clinical outcomes, today enabling most affected infants and children to live well into adulthood. Ongoing evolution of the technology (including three-dimensional TEE) promises to maintain this imaging approach at the forefront of clinical practice. Competent performance of TEE in the patient with CHD, however, requires a number of essential technical and cognitive skills, in addition to a solid understanding of the broad spectrum of congenital pathology. Thus, the important need for a comprehensive reference on the subject to assist specialists who care for these patients. Transesophageal Echocardiography for Congenital Heart Disease represents a unique work, the only textbook of its kind that focuses specifically upon the applications of TEE in CHD. In each chapter, the contributors$1 (Bhighly regarded specialists and leaders in the field$1 (Bprovide practical and instructive information on the many different aspects of CHD evaluation by TEE. The textbook is extensively supplemented with over 700 figures/illustrations and more than 400 high quality videos (available online). This reference will prove an invaluable resource for those who use TEE in the care of both children and adults with CHD, whether they be cardiologists, surgeons, anesthesiologists, intensivists, sonographers, or trainees wishing to obtain basic knowledge or advance their understanding of the field.s
Science of Ultrasound and Echocardiography -- Instrumentation -- Indications and Guidelines for Performance of Transesophageal Echocardiography in Congenital Heart Disease and Pediatric Acquired Heart Disease -- Structural Evaluation of the Heart by Transesophageal Echocardiography -- Functional Evaluation of the Heart by Transesophageal Echocardiography -- Systemic and Pulmonary Venous Anomalies -- Atrial Abnormalities and Atrial Septal Defects -- Atrioventricular Septal Defects and Atrioventricular Valve Anomalies -- Ventricular Septal Defects -- Evaluation of the Single Ventricle -- Outflow Tract Anomalies -- Evaluation of Conotruncal Abnormalities -- Great Artery and Other Vascular Abnormalities -- Congenital Coronary Artery Anomalies -- Intraoperative and Postoperative Transesophageal Echocardiography in Congenital Heart Disease -- Additional Applications of Transesophageal Echocardiography -- Applications of Transesophageal Echocardiography in the Cardiac Catheterization Laboratory -- Transesophageal Echocardiography in Adults with Congenital Heart Disease -- Transesophageal Three-Dimensional Echocardiography in Congenital Heart Disease -- Clinical Applications of Three-Dimensional Transesophageal Echocardiography in Congenital Heart Disease.
Keywords: Medicine; Emergency medicine; Radiology, Medical; Cardiology; Pediatrics; Heart -- Surgery; Medicine & Public Health; Cardiology; Imaging / Radiology; Diagnostic Radiology; Pediatrics; Emergency Medicine; Cardiac Surgery